Description of a new species of Trichogypsiidae (Porifera, Calcarea) and first record of the genus in the Pacific Ocean - Lehnert, Helmut; Stone, Robert P. (Zootaxa, 2017)
A new species of Trichogypsiidae is described and compared to its congeners. Trichogypsia alaskensis n. sp. represents the fifth species of the family and with this record all three genera of the family are now represented in the North Pacific Ocean. Calcarea are rare in the Gulf of Alaska but with this new record the number of confirmed species rises from two to three. The new species has larger diactines of a broader size range and with a different pattern of spination than all congeners.